Implementation Of Project Based Learning (PjBL) Method On Music Learning In Junior High School Regina Pacis Surakarta (Jurnal Seni Musik, 2022)
Learning methods used to teach in online classes provide solutions so students can continue to understand the material presented, have appreciation and innovate in participating in teaching and learning activities. The project based learning method is a learning method that involves a project or activity as a medium in the learning process. This method focuses on student activities to be able to understand a concept and principle by conducting in-depth research on a problem and finding relevant solutions. This learning method makes students active, independent in learning, can apply the knowledge they already have, practice various thinking skills, attitudes, and concrete skills. Meanwhile, for complex problems, learning is required through investigation, collaboration and experimentation in making a project, as well as integrating various subjects (materials) in learning. Teachers at Regina Pacis Junior High School Surakarta use project based learning methods in their learning. The teachers at the junior high school combined 3 lessons to make one project. The research method used in this study is qualitative with descriptive exposure. The research subjects were music teachers at Regina Pacis Junior High School, Surakarta. The results of data collection using observation, interview, documentation, and data analysis techniques. The data analysis technique is divided into three stages, namely data reduction, data presentation, and drawing conclusions. The results of interviews and observations that have been collected include documentation, pictures, photos, videos, field notes, personal notes, and other documents after being studied, examined and researched and then reduced to an abstraction.